An inverse problem with final overdetermination for a quasilinear parabolic equation with an unknown right-hand side - Gol’dman, N.L. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2003)
The questions of uniqueness of an exact solution in H"older classes and the construction of stable approximate solutions are considered for the inverse problem on determination of an unknown right-hand side in a quasilinear parabolic equation of the general type with the use of additional information given at final time.